PENETAPAN HARGA TRANSFER DALAM KAJIAN PERPAJAKAN - Gusnardi ' (Program Studi Pendidikan Ekonomi Universitas Riau, 2012)
ransaction transfer of pricing in general in management accounting applied tomeasure affiliating division performance or corporate subsidiaries. But transactionmultinational intracorporate transfer of pricing maximization of group efficiencyapplicable to in totality, and motivation of minimization of global tax load of they, withimplication the happening of friction of production from state having high tax rate tostate having minimum or low tax rate.